Absence of NOTCH1 mutation and presence of CDKN2A deletion predict progression of esophageal lesions. Issue 1 (30th June 2022) - Liu, Mengfei; Liu, Ying; Zhou, Ren; Liu, Zhen; Guo, Chuanhai; Xu, Ruiping; Li, Fenglei; Liu, Anxiang; Yang, Haijun; Zhang, Sanshen; Shen, Lin; Duan, Liping; et al.
Abstract: Currently, surveillance for esophageal squamous cell carcinoma (ESCC) runs a risk of underestimation of early lesions which show absence of iodine staining, with no or only mild histologic changes. The development of molecular markers that indicate risk of progression is thus warranted. We performed whole‐exome sequencing on biopsies from two sequential endoscopies of a single esophageal lesion and matching blood samples. There were 27 pairs of age‐, gender‐, pathologic stage‐, and sampling interval‐matched progressors and non‐progressors identified in a prospective community‐based ESCC screening trial. Putative molecular progression markers for ESCC were first evaluated by comparing somatic mutation, copy number alteration (CNA), and mutational signature information among progressors and non‐progressors. These markers were then validated with another 24 pairs of matched progressors and non‐progressors from the same population using gene alteration status identified by target sequencing and quantitative PCR. Progressors had more somatic mutation and CNA burden, as well as apolipoprotein B mRNA editing catalytic polypeptide‐like and age‐related signature weights compared with non‐progressors. A gene score consisting of somatic NOTCH1 mutation and CDKN2A deletion is predictive of risk of progression in lesions which show absence of iodine staining under endoscopy but have no or only mild dysplasia. This gene score was also validated in an external cohort of matched progressors and non‐progressors. Absence of NOTCH1 mutation and presence of CDKN2A deletion are markers of progression in squamous lesions of the esophagus. This gene score would be an ideal indicator for assisting the pathologist in the identification of high‐risk individuals who could be potentially 'missed' or subject to a risk underestimation by histologic analysis, and might improve the performance of ESCC surveillance. © 2022 The Pathological Society of Great Britain and Ireland.